Bispecific antibody for lung cancer: mechanisms and clinical insights - Chen, Wei; Zhou, Afang; Zhou, Yunfeng (Frontiers in Immunology, 2025)
Lung cancer is a refractory malignancy. Although various therapeutic options, including targeted therapies, immune checkpoint inhibitors, and systemic chemotherapy, have significantly improved the prognosis of lung cancer patients, five-year survival rates are still low. Bispecific antibodies have attracted much attention because of their ability to bind different antigens or epitopes on the same antigen at once and because of their multiple novel functional mechanisms. Recently, three bispecific antibodies have been successively approved for lung cancer treatment, demonstrating the potential of bispecific drugs in lung cancer therapy. Various bispecific antibodies are currently under clinical trials to evaluate their safety and efficacy in lung cancer. In this review, we provide an overview of these antibodies’ structure and mechanism of action, summarize their clinical progress in lung cancer treatment, and discuss and analyze the challenges and future directions of bsAbs application in lung cancer.